The Effect of Magnesium Supplementation on Vascular Calcification in CKD: A Randomized Clinical Trial (MAGiCAL-CKD) - Bressendorff, Iain; Hansen, Ditte; Schou, Morten; Kragelund, Charlotte; Svensson, My; Hashemi, Bahram; Kristensen, Tilde; Vrist, Marie Houmaa; Borg, Rikke; Tougaard, Birgitte; Borg, Kristine; Hjortkjær, Henrik Øder; et al. (Journal of the American Society of Nephrology, 2023)
Significance StatementMagnesium prevents vascular calcification in animals with CKD. In addition, lower serum magnesium is associated with higher risk of cardiovascular events in CKD. In a randomized, double-blinded, placebo-controlled trial, the authors investigated the effects of magnesium supplementation versus placebo on vascular calcification in patients with predialysis CKD. Despite significant increases in plasma magnesium among study participants who received magnesium compared with those who received placebo, magnesium supplementation did not slow the progression of vascular calcification in study participants. In addition, the findings showed a higher incidence of serious adverse events in the group treated with magnesium. Magnesium supplementation alone was not sufficient to delay progression of vascular calcification, and other therapeutic strategies might be necessary to reduce the risk of cardiovascular disease in CKD.BackgroundElevated levels of serum magnesium are associated with lower risk of cardiovascular events in patients with CKD. Magnesium also prevents vascular calcification in animal models of CKD.MethodsTo investigate whether oral magnesium supplementation would slow the progression of vascular calcification in CKD, we conducted a randomized, double-blinded, placebo-controlled, parallel-group, clinical trial. We enrolled 148 subjects with an eGFR between 15 and 45 ml/min and randomly assigned them to receive oral magnesium hydroxide 15 mmol twice daily or matching placebo for 12 months. The primary end point was the between-groups difference in coronary artery calcification (CAC) score after 12 months adjusted for baseline CAC score, age, and diabetes mellitus.ResultsA total of 75 subjects received magnesium and 73 received placebo. Median eGFR was 25 ml/min at baseline, and median baseline CAC scores were 413 and 274 in the magnesium and placebo groups, respectively. Despite plasma magnesium increasing significantly during the trial in the magnesium group, the baseline-adjusted CAC scores did not differ significantly between the two groups after 12 months. Prespecified subgroup analyses according to CAC>0 at baseline, diabetes mellitus, or tertiles of serum calcification propensity did not significantly alter the main results. Among subjects who experienced gastrointestinal adverse effects, 35 were in the group receiving magnesium treatment versus nine in the placebo group. Five deaths and six cardiovascular events occurred in the magnesium group compared with two deaths and no cardiovascular events in the placebo group.ConclusionsMagnesium supplementation for 12 months did not slow the progression of vascular calcification in CKD, despite a significant increase in plasma magnesium.Clinical Trials Registrationwww.clinicaltrials.gov (NCT02542319).